The Role of Cadres in Improving the Health of Pregnant Women Regarding Drinking Compliance Fe Tablets and Folic Acid - Papat Patimah; Sifa Fauziah; Obar Obar (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
Pregnant women should consume Fe during pregnancy, in addition to consuming folic acid. The function of folic acid can increase the enzymes alanine aminotransferase (ALT), aspartate transaminase (AST), and glutamyl transpeptidase (GGT) which are important for metabolism in the liver. Design of the study used generic exploratory research design. This study investigated the role of cadres in improving the health of pregnant women regarding compliance with taking Fe and folic acid tablets Method Data collection techniques used in-depth interviews with freer questions than semi-structured interviews with in-depth interviews. Testing the validity of the interview guidelines using pilot interviews Results were focus of cadre activities during posyandu and Factors influencing cadres to play an active role. In Conclusion, the role of health cadres is less effective. This is due to factors that influence the role of cadres, namely the lack of knowledge of cadres regarding the benefits and impacts of taking FE tablets and folic acid for pregnant women, the cadres are still waiting for instructions from the midwife.